Determination of bisphenol A in water bottles by spectrophotometric method - Razak, Nur Syuhada Abd (Universiti Sains Malaysia, 2015)
Bisphenol A (BpA) is a building block for the production of epoxy resins and polycarbonate plastics. These plastics are extensively employed to produce water bottles from which BpA can leach into drink. Therefore this dissertation aims to determine the trace amounts of BpA leached from water bottled samples with respect to different temperatures of water (0°C, 4°C, 27°C, 70°C and 100°C) and after being repeatedly used by using UV-Vis spectrophotometry method. A total of three plastic water bottles were randomly chosen for this purpose. The analysis of BpA was carried out by diazotizing the clenbuterol with sodium nitrite before coupled them with BpA to form an azo-compound in ammonia-ammonium chloride buffer. Then, the solution was subjected to UV Spectra at 396 nm. For the effect of different water temperatures, the trace amounts of BpA can be detected from Bottle 3 at 0°C (0.006 mM), 4°C (0.0041 mM), 100°C (0.0014 mM) and no BpA was detected at 27°C and 70°C. While, Bottle 1 and 2, there is also no BpA was detected at any temperatures of water samples. The reusability test was also conducted for all three types of bottles. Bottle 3 showed no BpA was detected for the first time of use, however about 0.0015 mM of BpA was detected after second times of use and 0.0058 mM of BpA after the third times. For Bottle 1, the trace amounts of BpA was found after had been used for three times (0.0025 mM). This study was successfully conducted to show the potential of BpA to leach from the plastic bottle at different water temperatures and after the bottle being repeatedly used.